The Efficacy of Topical Tranexamic Acid in Breast Surgery Evaluating the Drain Output and Complications Reduction: A Systematic Review and Meta-Analysis - Sudarman, Jesica Putri; Sayudo, Iqbal Farhan; Putri, Marcelvina Mutiara; Ali, Gary; Handini, Nurliati Sari (Jurnal Plastik Rekonstruksi, 2024)
Introduction : The topical administration of Tranexamic Acid (TXA) has gained significant attention for its potential advantages in various plastic surgery procedures. This study aims to conduct a systematic review and meta-analysis focusing on the use of topical TXA in breast surgery, analysing its impact on postoperative drain output and complications. Method : PubMed, Embase and the Cochrane Library databases were systematically searched to identify relevant studies. The data synthesis utilized random-effects models and the findings were presented as a mean difference and weighted odds ratio along with the corresponding 95% confidence interval. Results : Seven studies including four RCTs and three observational studies, comprising 1,553 breasts undergoing surgery were included. The average age of participants was 46 years; mean body mass index (BMI) was 26.1 kg/mm2. Of the breasts studied, 764 (49%) received topical TXA and 789 (51%) received normal saline as placebo. Overall, topical TXA was associated with a lower drain output in the first 24 hours postoperative (MD -25.87; p=0.00001) and a lower cumulative drain output (MD -59.72; p<0.00001). The rate of hematoma is significantly lower in the topical TXA group compared to the control group (OR 0.19; p=0.0009). There were no significant differences in rates of seroma, infection, thromboembolic events and time to drain removal between groups.   Conclusion: Evidence of this study suggests that administration of topical TXA significantly reduces the drain output production and hematoma in breast surgery. The use of topical TXA not significantly affecting rates of seroma, infection and postoperative duration with drain.